1994
DOI: 10.1002/j.1460-2075.1994.tb06617.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for stability of the chloroplast psbD RNA are located within its short leader region in Chlamydomonas reinhardtii.

Abstract: Stability of the chloroplast psbD mRNA encoding the D2 protein of the photosystem II reaction center is drastically decreased in the nuclear photosynthetic mutant nac2‐26 of Chlamydomonas reinhardtii. Using biolistic transformation and genetic crosses we have introduced chimeric genes consisting of the psbD leader fused to a reporter gene into the chloroplast in both wild‐type and mutant nuclear backgrounds. The chimeric message is destabilized in the latter, but not in the former case, indicating that the 74 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 41 publications
2
150
1
Order By: Relevance
“…Our previous studies (Surzycki et al, 2007) have already shown that artificial regulation of the chloroplast psbD mRNA of the PSII D2 reaction center protein can be achieved by placing the nuclear Nac2 gene under the control of the copper-repressible nuclear Cyc6 promoter (Merchant and Bogorad, 1987). In this system, conditional repression of chloroplast gene expression is based on the fact that the major target site of Nac2 is within the 59-untranslated region (59UTR) of the psbD mRNA and that this region is sufficient to confer Nac2-dependent expression for any chloroplast gene when it is driven by the psbD 59UTR (Nickelsen et al, 1994). Although this system can be used for controlling expression of a heterologous gene (Surzycki et al, 2007), we have not succeeded in using it for the analysis of essential chloroplast genes.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies (Surzycki et al, 2007) have already shown that artificial regulation of the chloroplast psbD mRNA of the PSII D2 reaction center protein can be achieved by placing the nuclear Nac2 gene under the control of the copper-repressible nuclear Cyc6 promoter (Merchant and Bogorad, 1987). In this system, conditional repression of chloroplast gene expression is based on the fact that the major target site of Nac2 is within the 59-untranslated region (59UTR) of the psbD mRNA and that this region is sufficient to confer Nac2-dependent expression for any chloroplast gene when it is driven by the psbD 59UTR (Nickelsen et al, 1994). Although this system can be used for controlling expression of a heterologous gene (Surzycki et al, 2007), we have not succeeded in using it for the analysis of essential chloroplast genes.…”
Section: Introductionmentioning
confidence: 99%
“…Plastid genomes of higher plants and algae code for 100-150 proteins, most of which have a function in photosynthetic electron transport, ATP synthesis, or translation+ Their messenger RNAs have been found to be relatively long-lived, having transcript-specific halflives that range from a few hours to more than a day (Salvador et al+, 1993a)+ In addition to having transcriptspecific longevities, chloroplast mRNAs have been found to alter in stability during development (Klein & Mullet, 1987), in response to external factors, for example, light (Simpson & Herrera-Estrella, 1990;Salvador et al+, 1993a), and during endogenously controlled rhythms (Salvador et al+, 1993a;Hwang et al+, 1996)+ The components of the molecular machinery that degrades mRNAs in chloroplasts are not known+ Homologs of the rne gene encoding RNase E, the principal endoribonuclease thought to be involved in mRNA degradation in prokaryotes (Grunberg-Manago, 1999;Rauhut & Klug, 1999), were found in three algal plastid genomes-Porphyra purpurea (Reith & Munholland, 1995), Nephroselmis olivacea (Turmel et al+, 1999), and Guillardia theta (Douglas & Penny, 1999)-(out of 16 genomes sequenced to date), suggesting a role of this enzyme in chloroplast mRNA breakdown+ In Chlamydomonas, insertion of a poly(G) cassette, which impedes movement of exoribonucleases along RNA molecules, into the 59 untranslated regions (UTRs) of the pet D (Drager et al+, 1998(Drager et al+, , 1999 and psbB (Vaistij et al+, 2000) genes protected transcripts against rapid degradation, suggesting the involvement of a 59-to-39 exoribonuclease in mRNA decay in chloroplasts+ In addition to factors acting at the 59 ends of mRNAs, factors at the 39 ends of chloroplast transcripts appear to be important for mRNA stability+ Oligo(A) tails, supposed to be involved in bacterial mRNA decay (Sarkar, 1997;Grunberg-Manago, 1999), have been detected at the 39 termini of chloroplast transcripts of Chlamydomonas (Komine et al+, 2000) and spinach (Lisitsky et al+, 1996), suggesting an oligo(A)-dependent pathway of mRNA degradation in chloroplasts (Hayes et al+, 1999)+ Intramolecular determinants of mRNA longevity and the molecular mechanisms responsible for control of mRNA turnover in chloroplasts are largely unknown+ A number of studies show that the 59 UTRs of chloroplast transcripts contain sequences that are crucial for mRNA stability (Salvador et al+, 1993b;Nickelsen et al+, 1994;Eibl et al+, 1999;…”
Section: Introductionmentioning
confidence: 99%
“…No differences in transcript abundance were detected (S. Abrahamson, personal communication; A. DeLisle, personal communication). Other proteins binding to the 5' end of chloroplast transcripts have been implicated in translational initiation and stability in Chlamydomonas (Nickelsen et al, 1994;Zerges and Rochaix, 1994;Mayfield et al, 1995;Yohn et al, 1996). If hcf5 were defective in a protein required for the translatability of a number of chloroplast messages while affecting the stability of only certain ones, it could account for the pleiotropic effects of this mutation on PSI, PSII, and the Cyt complex.…”
Section: Discussionmentioning
confidence: 99%